ОЦІНКА ВАРТОСТІ ПОСЛУГ ДОБОВОГО РЕГУЛЮВАННЯ ЕЛЕКТРОСПОЖИВАННЯ НЕМАНЕВРЕНИМИ НАКОПИЧУВАЧАМИ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Парус, Є.В.; Блінов, І.В.; Костіков, А.О. (Інститут електродинаміки Національної академії наук України, 2023)
The publication is devoted to the basics of calculating the economic effect of providing energy storage systems with the service of compensation the surplus of electric energy generation by nuclear power plants with small modular reactors at night. The main components of the mathematical model for calculating the service tariff for the accumulation of a surplus of energy generation are considered. A simulation model of the functioning of the energy storage system is given. A mathematical model was developed for calculating the minimum tariff for the service of compensation for the surplus of electricity generation by nuclear power plants with small modular reactors in the night hours using energy storage systems. Bible 15.